PWE-055 Endoscopic Ultrasound Guided Radiofrequency Ablation (EUS-RFA) for Pancreatic Ductal Adenocarcinoma. (4th June 2013) - Pai, M; Yang, J; Zhang, X; Jin, Z; Wang, D; Senturk, H; Lakhtakia, S; Reddy, D N; Kahaleh, M; Habib, N; Brugge, W R
Abstract : Introduction: The five year survival for pancreatic ductal adenocarcinoma (PDAC) is less than 5% in spite of the advances in management of cancers in the last few decades. Even though surgical resection remains the only potentially curative treatment for PDAC, only 10–20% of patients are candidates for pancreatic resection with almost 50% of patients having distant spread of tumour and approximately one-third manifesting locally advanced disease. Kahaleh and colleagues have demonstrated that EUS guided RF ablation (EUS-RFA) of the pancreatic head using Habib EUS-RFA catheter (Emcision Ltd, UK) was well tolerated in 5 Yucatan pigs and with minimal pancreatitis (1). The aim of this report is to outline the feasibility, safety, complications and early results of EUS-RFA using Habib catheter in patients with inoperable PDAC. Methods: Seven patients underwent EUS-RFA of PDAC. A novel monopolar radiofrequency (RF) catheter (1.2 mm Habib EUS-RFA catheter, Emcision Ltd, London) was placed through a 19 or 22 gauge fine needle aspiration (FNA) needle after FNA was performed. Results: Seven patients had EUS-RFA of PDAC with a median age of 69 (range 50 – 77) years. There were 3 female and 4 male patients. Five patients had PDAC in the head of pancreas whilst two had in the body of pancreas. RF was applied at 5 watts, 10 watts and 15 watts in an incremental manner in 1, 3 and 3 patients respectively. The median number of applications were 3 (range 2 – 4) and each application was 90 seconds. The EUS-RFA was completed in all patients. The mean size was 35.2mm and the post procedure imaging in 3–6 months showed decrease in size of the lesion in two patients, whilst the lesions were unchanged in the rest of the patients. There were no early complications like injury or perforation of duodenal or gastric wall, bleeding or severe pancreatitis. All patients stayed overnight after the procedure for observation and four were discharged next day and there were no readmissions post procedure due to pain. One patient had mild pancreatitis which settled with conservative management and was discharged 3 days post procedure. Conclusion: EUS- RFA of PDAC with a novel monopolar RF probe was well tolerated in 7 patients. The initial results suggest that the procedure is technically relatively easy and safe Disclosure of Interest: M. Pai: None Declared, J. Yang: None Declared, X. Zhang: None Declared, Z. Jin: None Declared, D. Wang: None Declared, H. Senturk: None Declared, S. Lakhtakia: None Declared, D. N. Reddy: None Declared, M. Kahaleh: None Declared, N. Habib Shareholder of: EMcision Limited, London, United Kingdom, Conflict with: Director, EMcision Limited, London, United Kingdom, W. Brugge: None Declared. Reference: Gaidhane M et.al . Endoscopic Ultrasound-Guided Radiofrequency Ablation (EUS-RFA) of the Pancreas in a Porcine Model. Gastroenterol Res Pract. 2012; 431451.